Reformasi Administrasi Publik dalam Berbagai Perspektif - Hamdan (Universitas Brawijaya, Indonesia, 2009)
State Administration Reformation, these days becoming more focus. There are two twinning issues in government apparatus activity in most developing country. Fist, government bureaucracy supposed as a big boat able to save all society citizen entirely from political and also economic floods